Identification of CaPs locus involving in purple stripe formation on unripe fruit, reveals allelic variation and alternative splicing of R2R3-MYB transcription factor in pepper (Capsicum annuum L.) - Li, Ning; Liu, Yabo; Yin, Yanxu; Gao, Shenghua; Wu, Fangyuan; Yu, Chuying; Wang, Fei; Kang, Byoung−Cheorl; Xu, Kai; Jiao, Chunhai; Yao, Minghua (Frontiers in Plant Science, 2023)
Anthocyanin biosynthesis is controlled by a clade of R2R3-MYB transcription factors. In this study, we identified the CaPs locus as a novel allelic variation of the R2R3-MYB transcription factor CaAN3, which causes the formation of purple stripes on the exocarp of unripe fruit in pepper (Capsicum annuum L.). We performed a bulked segregant analysis of the purple striped trait using an F2 population derived from a cross between the mature purple striped fruit line Chen12-4-1-1-1-1 and the normal green fruit line Zhongxian101-M-F9. We mapped the CaPs locus to an 841.39 kb region between markers M-CA690-Xba and M-710-03 on chromosome 10. CA10g11690 encodes an R2R3-MYB transcription factor that is involved in the biosynthesis of anthocyanins as the best candidate gene. Overexpression and silencing in transformed tobacco (Nicotiana tabacum) lines indicated that CA10g11690 is involved in the formation of purple stripes in the exocarp. A comparison of parental sequences identified an insertion fragment of 1,926 bp in the second intron region of Chen12-4, and eight SNPs were detected between the two parents. Additionally, there were 49 single nucleotide polymorphic variations, two sequence deletions, and four sequence insertions in the promoter region. We found that CA10g11690 undergoes alternative splicing and generates different transcripts. Thus, the functional transcript of CA10g11690 appeared to be primarily involved in the development of purple phenotype in the exocarp. Our data provide new insight into the mechanism of anthocyanin biosynthesis and a theoretical basis for the future breeding of purple striped pepper varieties.